2014
DOI: 10.1073/pnas.1412327111
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the dynamic changes of 5-hydroxymethylcytosine in T-cell development and differentiation

Abstract: The discovery of Ten Eleven Translocation proteins, enzymes that oxidize 5-methylcytosine (5mC) in DNA, has revealed novel mechanisms for the regulation of DNA methylation. We have mapped 5-hydroxymethylcytosine (5hmC) at different stages of T-cell development in the thymus and T-cell differentiation in the periphery. We show that 5hmC is enriched in the gene body of highly expressed genes at all developmental stages and that its presence correlates positively with gene expression. Further emphasizing the conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
171
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(196 citation statements)
references
References 53 publications
25
171
0
Order By: Relevance
“…Given the existence of relatively easy approaches to perform in vitro differentiation and selection of well-characterized types of hematopoietic cells, substantial data has been accumulated to favor the role of 5hmC in transcriptional programming of myeloid and lymphoid differentiation ( Table 1). Globally, a drop in 5hmC levels has been described during differentiation from hematopoietic stem cells (HSCs) [36], except for one study showing overall 5hmC increase (without genome context data) [37]. Despite this global reduction, 5hmC remains enriched at particular loci, matching the distribution shown by earlier studies (i.e., promoters and gene bodies).…”
Section: Specific 5-hydroxymethylcytosine Enrichment Identifies Bloodmentioning
confidence: 56%
See 1 more Smart Citation
“…Given the existence of relatively easy approaches to perform in vitro differentiation and selection of well-characterized types of hematopoietic cells, substantial data has been accumulated to favor the role of 5hmC in transcriptional programming of myeloid and lymphoid differentiation ( Table 1). Globally, a drop in 5hmC levels has been described during differentiation from hematopoietic stem cells (HSCs) [36], except for one study showing overall 5hmC increase (without genome context data) [37]. Despite this global reduction, 5hmC remains enriched at particular loci, matching the distribution shown by earlier studies (i.e., promoters and gene bodies).…”
Section: Specific 5-hydroxymethylcytosine Enrichment Identifies Bloodmentioning
confidence: 56%
“…Despite this global reduction, 5hmC remains enriched at particular loci, matching the distribution shown by earlier studies (i.e., promoters and gene bodies). In addition, 5hmC enrichment has been described in enhancers [19,36,[38][39][40][41] and lineage-specific TF binding sites [42,43]. In line with this, 5hmC changes are overrepresented in highly transcribed genes.…”
Section: Specific 5-hydroxymethylcytosine Enrichment Identifies Bloodmentioning
confidence: 59%
“…In support of this hypothesis, 5hmC is present at the highest levels in gene bodies of the most highly expressed genes (43,(56)(57)(58)(59)(60), and TET proteins have been linked to many processes and histone modifications associated with transcriptional variability. (i) In yeast, the Set2 methyltransferase complex travels with RNA Pol II and methylates H3K36 in gene bodies; the H3K36me3 modification is recognized by the Sin3a/Rpd3 histone deacetylase (HDAC) complex, which permits nucleosome reassembly by deacetylating lysines on histones 3 and 4, thus preventing spurious initiation at intragenic sites (53).…”
Section: Discussionmentioning
confidence: 92%
“…(i) In yeast, the Set2 methyltransferase complex travels with RNA Pol II and methylates H3K36 in gene bodies; the H3K36me3 modification is recognized by the Sin3a/Rpd3 histone deacetylase (HDAC) complex, which permits nucleosome reassembly by deacetylating lysines on histones 3 and 4, thus preventing spurious initiation at intragenic sites (53). In mammalian cells, TET functions are linked to both types of histone modifications: high levels of 5hmC are present in the gene bodies of expressed genes; 5hmC distribution in gene bodies is strongly correlated with that of H3K36me3 (43,(56)(57)(58)(59)(60); and TET1 coimmunoprecipitates with SIN3A and HDAC1/2 in mouse ES cells (61). (ii) Also in yeast, H2B ubiquitylation has been implicated in nucleosome dynamics (54,55), and a screen for chromatin regulators that altered the variability of reporter expression in yeast showed that H2B ubiquitylation recruited the Set3C HDAC complex, thereby limiting the high rate of Pol II elongation associated with transcriptional bursts (49).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that IDH2/R140Q-mediated repression of TET reduces 5hmC modification of Ebf1 and Spib. In T-cell development, 5hmC modification reportedly positively correlates with gene expression (41). It is possible that similar transcriptional control mechanisms operate in NIDF-AML cells.…”
Section: Discussionmentioning
confidence: 97%